2017
DOI: 10.4236/jbise.2017.105019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Traction Position in Cervical Traction Therapy Based on Dynamic Simulation Models

Abstract: This study describes the development of a cervical traction therapy simulation model that evaluates two types of the traction positions, namely the sitting position and the inclined position. An anatomically correct human skeleton model and two mechanical traction device models were constructed in simulations using a physics engine. The anterior and posterior intervertebral separations were measured at both positions with a series of traction forces (60N to 200N) and traction angles (10˚ to 40˚). The result su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Wong LKF et al suggested cervical traction in incline position for better improvement. 29 In the present series, traction was given in 15º inclined posture which also a factor for important of our patients. Cervical traction stretches the posterior cervical region and to enlarge the interspaces at the intervertebral foramina.…”
Section: Discussionmentioning
confidence: 86%
“…Wong LKF et al suggested cervical traction in incline position for better improvement. 29 In the present series, traction was given in 15º inclined posture which also a factor for important of our patients. Cervical traction stretches the posterior cervical region and to enlarge the interspaces at the intervertebral foramina.…”
Section: Discussionmentioning
confidence: 86%
“…The traction method for treatment of AJD is a novel technique adopted that is increasingly used in clinical practice (9)(10)(11). This method is thought to reduce cervical vertigo compared with the traditional method.…”
Section: Introductionmentioning
confidence: 99%